Project scheduling with limited resources - Kiana Ahghari (مهندسی و مدیریت ساخت, 2020)
The scheduling of a project with limited resources is a matter of NP. One of the innovative approaches to solving this problem is to use prioritization rules in the planning of activities. In this article, we have implemented eleven rules of prioritization in a static and parallel way, and compared these methods with the criteria for completing the project in a shorter time period, by comparing 112 of the 130 standard test questions containing 30-120 activities. The results show that, firstly, the parallel approach to applying the rules of prioritization is more efficient than the series approach. Secondly, in order to take advantage of the more efficient parallel approach, only three arbitrary priority rules can be applied in parallel.Different resources such as time, capital, human resources, etc. are needed to carry out each activity. These resources are often divided into two types of renewable, such as human and non-renewable, such as capital. Each activity can be executed in several different modes, for example, manually, semi-mechanized or mechanized. The execution of each mode requires different types and amounts of resources